Parental health belief model constructs associated with oral health behaviors, dental caries, and quality of life among preschool children in China: a cross-sectional study - Liu, Shu-Mei; Xin, Yu-Meng; Wang, Feng; Lin, Pei-Chao; Huang, Hsiao-Ling (BMC oral health, 2024)
Early childhood caries (ECC) is a prevalent health problem that negatively affects both overall health and oral health-related quality of life (OHRQoL). This study investigated the association between health belief model (HBM) constructs and oral health behaviors, dental caries, and OHRQoL in preschool children in China. A total of 1562 preschool children aged 3 to 6 years were recruited from six public kindergartens in Hangzhou, Zhejiang Province, by using stratified cluster sampling. A questionnaire was administered to parents to collect information on demographics, HBM constructs, oral health behaviors, dental caries, and OHRQoL. Regression models were used to examine relationships between HBM constructs and the outcomes. Parental perceived benefits [adjusted odds ratio (AOR) = 1.47 and 1.42], perceived barriers (AOR = 0.65 and 0.63), and oral health self-efficacy (AOR = 20.59 and 19.09) were associated with brushing teeth twice daily and brushing teeth with parental assistance. Perceived susceptibility (AOR = 6.62) and perceived severity (AOR = 0.49) were significantly associated with children's ECC. Poorer oral health (β = 0.09), higher perceived susceptibility (β = 0.11), and greater perceived barriers (β = 0.30) were associated with lower OHRQoL. Brushing teeth twice daily (β = -0.19) and brushing teeth with parental assistance (β = -0.09) were associated with higher OHRQoL. Parental HBM constructs were significantly associated with oral health behaviors, ECC, and OHRQoL in preschool children. These findings indicate the importance of incorporating parental HBM constructs into health education programs to promote positive oral health behaviors, reduce the prevalence of caries, and enhance OHRQoL in preschoolers. Not applicable.